Solar Surgery Optical System Design - Munqith S. Dawood; Shaima'a Riyadh Tahhan (مجلة النهرين للعلوم الهندسية, 2012)
The sunlight is suggested to be used in solar surgery as an alternative to the laser surgery. The rays of powerful sunlight are collected, concentrated and transported to the operating theatre from outside through a system of optical fibers in order to use this solar energy in tumor and cancer cell evaporation instead of lasers. The idea of solar surgery is still new and need more practical and design enhancements. This study is a step on this way. A Schmidt Cassegrainien arrangement is suggested for this optical solar system design calculations. It consists of a parabolic dish to concentrate the solar radiation on a secondary flat mirror which directs the light into a fused silica optical fiber cable used to carry the concentrated solar beam from the concentrating system to the operation room.The parabolic reflector dish rim half angle was chosen to be 45o to realize high flux and high efficiency. MATLAB program (version 7.00) has been used to calculate the diameter of the primary parabolic dish, the diameter of the secondary flat mirror and its recession from the fiber tips by two design procedures. The first procedure of these calculations is based on starting with the choice of the optical fiber diameter, while the second design procedure is based on the choosing first the distal end diameter of the optical fiber.The calculations of the second procedure showed more practical results. As the most often used fiber distal diameter in surgery is 0.6mm, then according to calculations the diameter of the primary parabolic dish reflector will be 180mm with a focal length of 108.64mm. The small secondary mirror is perfectly flat of 10.5mm in diameter and its recession from the fiber tip is 5.27mm. Another MATLAB program has been written to find the suitable numerical aperture for the optical fiber of the concentrator system to reach maximum efficiency of the system. It was found to be 0.7 theoretically. The nearest available value of NA for fused silica fiber was 0.66. Fused silica optical fiber of 1mm for core diameter was chosen because of its ability to withstand the high degree of temperature. It is found that this optical system could deliver a flux density as high as 73Wmm-2 for contact surgery and 32Wmm-2 for noncontact surgery.